THE EFFECT OF CAPITAL ADEQUACY AND LENDING ON PROFITABILITY WITH CREDIT RISK AS A MODERATION VARIABLE - Vimala Gyasanggun Mahestika; Ika Rosyada Fitriati (Jurnal Ekonomi, 2023)
The purpose of this study is to determine the effect of capital adequacy and lending on profitability contributed by credit risk in Conventional General Banking Companies Listed on the Indonesia Stock Exchange Period Year 2017-2021. The method used is purposive sampling with a total sample of 119. The data analysis technique uses a multiple linear regression analysis model with the help of Eviews 10 software. The results of the analysis in this study show that the level of capital adequacy and lending negatively affects the profitability of Conventional General Banking Companies Listed on the Stock Exchange Indonesia for the 2017-2021 period. Credit risk has a negatively affects moderating capital adequacy to profitability in Conventional General Banking Companies Listed on the Indonesia Stock Exchange for the 2017-2021 Period. Then, credit risk also has a negatively affects lending to profitability in Conventional General Banking Companies Listed on the Indonesia Stock Exchange Period 2017-2021.